Cardiff bay: A coastal reservoir for urban regeneration - Falconer, Roger (IAHR, 2020)
The world faces considerable water management challenges now and increasingly in the future; primarily brought about by: the predicted impacts of climate change, the increasing need to provide more water, food and energy for a growing global population, and increasing globalisation leading to a wider global wealth distribution and a corresponding increase in demand for water, associated with the need for more commodities (such as cars, clothes) etc. In addition, in most countries world-wide there is an increasing population shift away from rural communities to larger urban cities, where there are better employment prospects, and with these cities often being located near the coast.